Anda di halaman 1dari 4

# Helpsheet

## Use this sheet to help you:

Recognize a quadratic expression and how to expand or factorise it Solve a quadratic expression using trial-and-error methods and also by using the formula Understand the relationship between the algebraic and graphical solution of a quadratic equation Recognize and solve simultaneous quadratic equations

This publication can be cited as: Carter, D. (2008), Quadratic Equations, Teaching and Learning Unit, Faculty of Business and Economics, the University of Melbourne. http://tlu.fbe.unimelb.edu.au/ Further credits: Beaumont, T. (content changes and editing), Pesina, J. (design and layout).

FACULTY OF

## BUSINESS & ECONOMICS

Helpsheet

Expanding pairs of brackets
(a + b)(c + d), (where a, b, c and d are unspecified constants) = ac + ad + bc + bd. *One way to help remember this is FOIL First, Outside, Inside, Last. Many expressions you will see are of the form (x + a)(x + b), multiplying this out gives x2 + (a + b)x + ab A quadratic expression contains an unknown x raised to the power 2, no higher or lower.

## Technique for factorising a quadratic expression

Remember: factorising is the reverse of expanding. e.g Factorise x2 + 12x + 32 Assume the factors are (x + a)(x + b). From this (x + a)(x + b) = x2 + (a + b)x + ab. From the expression given a + b = 12 and ab = 32. So look for two numbers whose sum is 12 and product is 32. By trial and error we find that 4 + 8 = 12 and 4 x 8 = 32, so we have the factors (x + 4) and (x + 8). Therefore the solution to the factorisation of x2 + 12x + 32 is (x + 4)(x + 8). Not all expressions can be factorised using this technique.

We are asked to solve the equation x2 + 12x + 32 = 0 From the previous example: x2 + 12x + 32 = (x + 4)(x + 8) Therefore we need to solve (x + 4)(x + 8) = 0. When ab =0, then either a = 0 or b = 0, So either x + 4 = 0 or x + 8 = 0, which gives x = -4 and x = -8 as solutions (also known as roots). You can check your answers by substituting each one in turn into the original equation. The general form of a quadratic equation is ax2 + bx + c = 0

Page 1

Helpsheet

## The formula for solving any quadratic equation

Using the trial and error method can be quite difficult and time consuming and relies heavily on guesswork. A formula exists for solving any quadratic equation. This takes us straight to the roots and will also tell us whether a solution exists. Given any quadratic equation ax2 + bx + c = 0 (where a, b and c are given constants) the solution (roots) are given by the formula x = - b (b2- 4ac) 2a e.g x2 + 12x + 32 = 0 from this we have a = 1, b = 12 and c = 32, substituting these values into the formula gives x = - 12 (122 4 x 1 x 32) 2x1 = -12 (144 128) 2 = - 12 16 2 x = - 12 + 4 or x = - 12 - 4 2 2 x = -4 or x = -8 (as found previously using trial and error method) In this example we found two roots, from this we can deduce that if b2- 4ac > 0, there will be two solutions Not all quadratics can be factorised. If b2- 4ac is a negative result, then we have to find a square root of a negative number, which we have seen earlier it has no square root. Therefore if b2- 4ac is negative there are no real roots to the equation. i.e. If b2- 4ac < 0, there is no solution. Some quadratics have only one root (solution). These are called perfect squares. e.g. x2 + 10x + 25 = 0. Using trial and error or the formula you will find (x + 5) (x + 5) = 0 or (x + 5)2 = 0 => x = -5 A perfect square occurs when b2- 4ac = 0. i.e. there will be one solution.

y = x2 + 12x + 32 is an example of a quadratic function. The general form of a quadratic function is y = ax2 + bx + c. (a, b, c are parameters) The graph of a quadratic function is a curve called a parabola. It is a U-shape arising from the fact that x2 is positive when x is either positive or negative. If the parameter a is positive then the U-shape has its two arm pointing upwards. If the parameter a is negative, then the U-shape has its two arms pointing downwards. The absolute value of a determines how steeply the curve turns up (or down). Page 2

Helpsheet

The constant term, c, determines the y intercept. The roots of the equation determine the x intercept(s). If there are no roots to the equation then the curve does not cross through the x-axis. i.e. in the case of a positive graph it will be wholly above the x-axis, and if it is a negative graph it will be wholly beneath the x-axis.

## The inverse quadratic function

x = y2 => y = x This is considered a relation, for to be a function requires that there be no more than one value of the dependent variable, y, associated with any given value of x. In order to satisfy this condition we split the relation and create two functions y = +x and y = -x

## Simultaneous quadratic equations

We can solve a pair of simultaneous equations in a similar way to solving linear equations. e.g. y = 2x2 + 3x + 2 (1) y = x2 + 2x + 8 (2) Let (1) = (2) 2x2 + 3x + 2 = x2 + 2x + 8 Collect all terms to the left hand side of the equation => x2 + x 6 = 0 Factorise the quadratic either by trial and error or use the formula => (x 2)(x + 3) = 0 => x = 2 or x = -3 Substitute each of the values into either equation to solve for y. Substitute x = 2 in (2) y = (2)2 + 2(2) + 8 => y = 16 Substitute x = -3 in (2) y = (-3)2 + 2(-3) + 8 => y = 11 To check that these values are correct, substitute them into equation (1). Given that the values are correct, our solution to the given equations are x = 2, y = 16 and x = -3, y = 11. We could show these solutions graphically by sketching the graphs. The solutions to a given pair of simultaneous equations are given by the coordinates of the points of intersection of the two curves.

Page 3